2021
DOI: 10.26430/chungarica.2021.51.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Premature ventricular complexes : Systematic review, evaluation and management

Abstract: Premature ventricular complexes (PVCs) are a common finding in general population and can be even considered physiologic in most cases. Nevertheless, very frequent isolated PVCs may lead to the development of a usually reversible left ventricular dysfunction or be a manifestation of an underlying cardiac condition that could be associated with more severe ventricular arrhythmias, heart failure or cardiac death. Three causative mechanisms of the PVCs have been proposed: abnormal automaticity, triggered activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It is typically considered benign and not causing any symptoms in most individuals (2). It has been linked to age, male gender, hypertension, smoking, caffeine use, and reduced physical activity (3). Although it is considered benign, recent studies have reported that low or high PVCs burden is associated with atrial fibrillation (AF), heart failure, and stroke-like symptoms such as numbness, weakness, loss of vision, conversation, comprehension, and stroke (4).…”
Section: Introductionmentioning
confidence: 99%
“…It is typically considered benign and not causing any symptoms in most individuals (2). It has been linked to age, male gender, hypertension, smoking, caffeine use, and reduced physical activity (3). Although it is considered benign, recent studies have reported that low or high PVCs burden is associated with atrial fibrillation (AF), heart failure, and stroke-like symptoms such as numbness, weakness, loss of vision, conversation, comprehension, and stroke (4).…”
Section: Introductionmentioning
confidence: 99%